School Teachers’ Knowledge about Epilepsy in Kathmandu Metropolitan City - Khanal, K.; Maharjan, R.; Pokharel, B.R.; Sanjel, S. (Kathmandu University Medical Journal, 2017)
Background Studies on Knowledge towards epilepsy among school teachers are very limited on developing countries especially with reference to Nepal. Level of knowledge of schoolteachers plays an important role on providing a greater educational support for epileptic child and to maintain good communication skills between epileptic and normal child. Objective Objective of this study is to assess the level of knowledge about epilepsy and its associated factors among school teachers. Method A cross sectional study was conducted from 10th June to 4th July, 2014 among 165 teachers teaching in six different schools of Kathmandu Metropolitan City. A self-administrated questionnaire consisting of structured and multiple choice questions were designed to collect information on the teacher’s socio-demographic profile and knowledge about epilepsy. A scoring system was developed for each question: each correct answer was given a score of 1, and a score of 0 for wrong answer. Total score was categorized on two categories: Good Knowledge and Poor Knowledge. Result Teacher’s age did not correlate significantly with their knowledge about epilepsy but total years of teaching experiences and knowledge about epilepsy were found to be positively correlated (ρ= 0.165, p= 0.01). Academic qualification of teachers and different teaching level were associated with level of knowledge (p= 0.023, p= 0.021). Significant difference on knowledge score was found among teachers having different academic qualification (p= 0.019). Conclusion All teachers were aware about epilepsy, but their knowledge about epilepsy was not sufficient therefore, health education training program about epilepsy is needed for teachers.